"Yes" in My Backyard? : The Economics of Refugees and Their Social Dynamics in Kakuma, Kenya - Sanghi, Apurva; Onder, Harun; Vemuru, Varalakshmi (World Bank, Washington, DC, 2017)
This report comes at a crucial time when the unprecedented global refugee crisis, most notably in Europe and the Mediterranean, has not only focused the world’s attention on the plight of refugees, but has also led to the politicization of refugee influxes. With an average of 24 people worldwide being displaced from their homes every minute of every day (UNHCR 2016), the debate surrounding the refugee crises is on the minds of many, ranging from governments and policy-makers to citizens, refugees, and host communities alike. Worldwide displacement is currently at an all-time high as war and persecution increase; one in every 113 people is now either a refugee, internally displaced, or seeking asylum (UNHCR 2016). In the past five years, at least 15 conflicts have erupted or reignited, and while protracted and harrowing wars have broken out in the Middle East, eight of these conflicts have been in Africa (Cote d’Ivoire, Central African Republic, Libya, Mali, Northeastern Nigeria, Democratic Republic of Congo, South Sudan, and Burundi) (UNHCR 2015). To compound matters, developing countries such as Lebanon, Jordan, Ethiopia, and Kenya are now hosting the largest share of refugees: they are home to nearly 90 percent of the world’s refugees (UNHCR 2016). This report, which provides an original analysis of the economic and social impact of refugees in Kenya’s Kakuma refugee camp on their Turkana hosts, therefore comes at an opportune time and could resonate with governments and policy makers beyond Kenya’s borders. In particular, the methodology authors have developed enables us to run policy scenarios in a rigorous manner, ranging from encampment to decampment (i.e. camp closure) scenarios, and the potential to apply this methodology in other refugee situations around the world is particularly advantageous.